Serine/Threonine Phosphatases in Atrial Fibrillation. (February 2017) - Heijman, Jordi; Ghezelbash, Shokoufeh; Wehrens, Xander H.T.; Dobrev, Dobromir
Abstract: Serine/threonine protein phosphatases control dephosphorylation of numerous cardiac proteins, including a variety of ion channels and calcium-handling proteins, thereby providing precise post-translational regulation of cardiac electrophysiology and function. Accordingly, dysfunction of this regulation can contribute to the initiation, maintenance and progression of cardiac arrhythmias. Atrial fibrillation (AF) is the most common heart rhythm disorder and is characterized by electrical, autonomic, calcium-handling, contractile, and structural remodeling, which include, among other things, changes in the phosphorylation status of a wide range of proteins. Here, we review AF-associated alterations in the phosphorylation of atrial ion channels, calcium-handling and contractile proteins, and their role in AF-pathophysiology. We highlight the mechanisms controlling the phosphorylation of these proteins and focus on the role of altered dephosphorylation via local type-1, type-2A and type-2B phosphatases (PP1, PP2A, and PP2B, also known as calcineurin, respectively). Finally, we discuss the challenges for phosphatase research, potential therapeutic significance of altered phosphatase-mediated protein dephosphorylation in AF, as well as future directions. Highlights: Atrial fibrillation (AF) is associated with profound atrial remodeling Global cardiomyocyte PP1, PP2A and calcineurin activities are increased in AF patients PP1, PP2A and calcineurin are involved in proarrhythmic atrial remodeling Methodological challenges exist to elucidate the precise roles of phosphatases in AF Phosphatases represent a potential therapeutic target for AF